Aplikasi Sistem Informasi CRM Berbasis Web - Firmansyah Kusasi; Bunga Paramita (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2022)
CRM (Customer Relationship Management) is a way how companies establish sustainable good relationships between companies and customers, communicate with customers, and market to them so as to ensure customer satisfaction and loyalty. The purpose of this study is to identify the phases in CRM, activities and roles of CRM Information Systems. An understanding of this topic will be a reference in designing and designing an efficient and effective CRM Information System application. CRM Information System has now been developed in the form of a web-based application. This means that the company does not have to buy a server to provide a CRM Information System but can develop it themselves using a CMS (Content Management System) based application. In operational activities, customer data is collected and stored in a database for analysis purposes. The data is then processed and analyzed automatically and in real time into useful information for strategic marketing decisions that are designed according to their respective divisions, be it Sales Force, Customer Service or Marketing.